Pengertian Teologis Gereja Berdasarkan Kitab-Kitab Taurat dan Implementasinya untuk Masa Kini - Agustinus Djali; Maswati Daya (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: Since the church was founded, it has been faced with problems. The fathers have tried to lay the foundation of church teachings very fundamentally, but until today it seems that the problems have not disappeared, instead there are deviations in both doctrine and service that open up gaps for misguidance and cause church growth to stagnate. Therefore, the church should immediately introspect and return to its basic principles, namely